(untitled) (Baghdad Science Journal, 2013)
The effects of solar radiation pressure at several satellite (near Earth orbit satellite, low Earth orbit satellite, medium Earth orbit satellite and high Earth orbit satellite ) have been investigated. Computer simulation of the equation of motion with perturbations using step-by-step integration (Cowell’s method) designed by matlab a 7.4 where using Jacobian matrix method to increase the accuracy of result.